Evaluation of the effectiveness of water dust-suppressing emulsions based on acrylic and alkyd polymers - Valeria V. Strokova; Anastasiya Yu. Ryazanova; Irina Yu. Markova; Margarita A. Stepanenko; Eduard M. Ishmukhametov (Записки Горного института, 2024)
Currently, the use of special dust-suppressing reagents is promising to reduce the level of dust in the vicinity and on the territories of pits, mining and processing plants and other facilities with a high content of fine dust. The analysis of ways to reduce the dust-forming ability of inorganic dispersions with a high degree of dusting is carried out. Due to the lack of regulatory and technical documentation devoted to the standardization of quality control methods for dust-suppressing compounds, it becomes necessary to analyze existing parameters and methods for their determination in order to develop mandatory methods for controlling the properties of dust-suppressing compounds, films formed by them and consolidated systems. The study is devoted to substantiating the necessary methods for assessing the dust-forming ability of inorganic dispersions after treatment with various dust suppressants and evaluating their effectiveness. The parameters are considered and methods for quantifying the determination of the quality of the consolidated layer of dust samples using different dust-suppressing compositions are described. As a result of the analysis of the set of parameter values, it was found that the most resistant to the effects of negative factors due to the formation of a denser and more durable polymer matrix mesh are dusting surface samples treated with an emulsion of alkyd glypthalic resin on a water basis with a high agglomerating effect on particles of inorganic dispersion and the formation of a consolidated layer with a wetting angle of 92.5° and a compressive strength 0.56 MPa.